Investor-State Dispute Settlement Mechanism in Vietnam’s New Generation Free Trade Agreements: Challenges and Recommendations - Thang, Nguyen Chi (Universitas Negeri Semarang, 2023)
In the recent years, Vietnam's attraction to foreign investment capital has increased rapidly. As a result, the disputes in the field of foreign investment have emerged more frequently. The fact that a dispute occurs between the government of the host country and a foreign investors, regardless of its cause, will bring adverse consequences to both parties. Amicable settlement of such disputes is an important factor to improve the efficiency of foreign investment, maintaining the trust between the host country and foreign investors. Therefore, stipulating commitments on the dispute settlement mechanism for international investment in multilateral free trade agreements such as Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), Vietnam - EU Investment Protection Agreement (EVIPA), and Regional Comprehensive Economic Partnership (RCEP) are indispensable. Therefore, in this context, the paper studies the investor-state dispute settlement (ISDS) mechanism in new-generation free trade agreements to which Vietnam is a member, namely EVIPA, CPTPP, RCEP; accordingly, the paper proposes some recommendations to Vietnam.